Study on positive-negative pressure seed metering device for wide-seedling-strip-seeding - Zhao, Xiaoshun; Bai, Wenjie; Li, Jincai; Yu, Huali; Zhao, Dawei; Yin, Baozhong (International Journal of Agricultural and Biological Engineering, 2022)
In order to solve the problem of poor uniformity of wheat strip sowing, this paper designs a positive-negative pressure wheat wide-seedling-strip-seeding precision seed metering device, which adopts the roller structure with the principle of combined positive-negative pressure. Through theoretical analysis and relevant data, the structure of the seed metering device and the structure of the positive-negative pressure air chamber were designed. The internal flow field conditions were simulated by Fluent software under different structural parameters. The design of the seed holes was completed by analyzing the pressure cloud diagram and the flow velocity vector diagram, and the optimal combination of parameters was obtained and the influence law of negative pressure on the flow field was obtained. The effect of rotational speed on the flow field was studied by EDEM-Fluent coupling technique. In this paper, a three-factor and three-level response surface test was conducted on a JPS-12 test bench with Liangxin-99 wheat as the research object. The experiment was conducted with the rotational speed of seed metering device, the negative pressure of seed suction and the seeding height as factors, and the qualified index, the reseeding index and the miss-seeding index as evaluation indicators. Through the test, the optimal structure and working parameters of the seed metering device were determined as follows: the diameter of the seed hole was 2 mm, and the number of seed holes per row was 28, negative pressure was −3.5 kPa, rotational speed of seed metering device was 19 r/min, and seeding height was 180 mm. Validation test was carried out on the optimized seed metering device: the qualified index was 80.62%, the reseeding index was 9.22%, and the miss-seeding index was 10.16%, which reached the parameter indicator in JB/T 10293-2013 Technical conditions of single seed (precision) seeder and met the agronomic requirements for wheat wide-seedling-strip-seeding. Keywords: wheat, precision, seed metering device, wheat wide-seedling-strip-seeding, positive-negative pressure, fluent, EDEM-Fluent coupling, response surface test DOI: 10.25165/j.ijabe.20221506.7261 Citation: Zhao X S, Bai W J, Li J C, Yu H L, Zhao D W, Yin B Z. Study on positive-negative pressure seed metering device for wide-seedling-strip-seeding. Int J Agric & Biol Eng, 2022; 15(6): 124–133.